Socioeconomic Status and School Type as Predictors of Academic Achievement - Hayri Eren Suna; Hande Tanberkan; Bekir Sıddık Gür; Matjaz Perc; Mahmut Özer (Journal of Economy Culture and Society)
We evaluated the effects of socioeconomic status and school type on academic achievement based on data from two million students over a 10 year period through three national transition systems in Turkey. Each of the three transition systems has its own national examination, and the data includes only students who took these exams. We used covariance analysis to compare the mean scores of public schools and private schools after controlling the effect of students’ socioeconomic levels. We found that students in private schools, who were socioeconomically stronger, had significantly higher academic achievement levels in language, mathematics, and science tests, and this finding was valid across all three transition systems. These effects were further exuberated when all the students were tracked by means of a national exam and placed into different high schools. It was found that the negative impact of one’s socioeconomic level on students’ scores reached its maximum value when all students were placed into high schools by means of a national exam. In all systems, the mean scores of private school students decreased significantly when the socioeconomic level was controlled. Our research has important implications for school tracking policies, specifically indicating that it would be better to omit or at least delay their deployment to post high-school education.